Cerebral Autoregulation Correlation With Outcomes and Spreading Depolarization in Aneurysmal Subarachnoid Hemorrhage. Issue 6 (24th February 2022) - Owen, Bryce; Vangala, Adarsh; Fritch, Chanju; Alsarah, Ali A.; Jones, Tom; Davis, Herbert; Shuttleworth, C. William; Carlson, Andrew P.
Abstract : Background: Delayed cerebral ischemia remains one of the principal therapeutic targets after aneurysmal subarachnoid hemorrhage. While large vessel vasospasm may contribute to ischemia, increasing evidence suggests that physiological impairment through disrupted impaired cerebral autoregulation (CA) and spreading depolarizations (SDs) also contribute to delayed cerebral ischemia and poor neurological outcome. This study seeks to explore the intermeasure correlation of different measures of CA, as well as correlation with SD and neurological outcome. Methods: Simultaneous measurement of 7 continuous indices of CA was calculated in 19 subjects entered in a prospective study of SD in aneurysmal subarachnoid hemorrhage undergoing surgical aneurysm clipping. Intermeasure agreement was assessed, and the association of each index with modified Rankin Scale score at 90 days and occurrence of SD was assessed. Results: There were 4102 hours of total monitoring time across the 19 subjects. In time-resolved assessment, no CA measures demonstrated significant correlation; however, most demonstrate significant correlation averaged over 1 hour. Pressure reactivity (PRx), oxygen reactivity, and oxygen saturation reactivity were significantly correlated with modified Rankin Scale score at 90 days. PRx and oxygen reactivity also were correlated with the occurrence of SD events. Across multiple CA measure reactivity indices, a threshold between 0.3 and 0.5 was most associated with intervals containing SD. Conclusions: Different continuous CA indices do not correlate well with each other on a highly time-resolved basis, so should not be viewed as interchangeable. PRx and oxygen reactivity are the most reliable indices in identifying risk of worse outcome in patients with aneurysmal subarachnoid hemorrhage undergoing surgical treatment. SD occurrence is correlated with impaired CA across multiple CA measurement techniques and may represent the pathological mechanism of delayed cerebral ischemia in patients with impaired CA. Optimization of CA in patients with aneurysmal subarachnoid hemorrhage may lead to decreased incidence of SD and improved neurological outcomes. Future studies are needed to evaluate these hypotheses and approaches.